2016
DOI: 10.1111/jocn.13361
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions for infertile couples: a critical review

Abstract: The implications of the review findings for the effective design of psychosocial interventions, including the content, format, duration and intervener for clinical practice are discussed. In confirming the efficacy of such intervention design, randomized controlled trials are needed to compare the interventions and usual care at clinical setting. Longitudinal design is also needed to examine the long-term effects of psychosocial interventions in infertile couples' well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 24 publications
2
45
0
1
Order By: Relevance
“…For example, Hämmerli et al's (2009) meta-analysis found psychological interventions were effective at improving ART pregnancy rates but did not reduce depression or anxiety. Chow et al (2016) recently found evidence that psychosocial interventions improved psychological and pregnancy outcome in their critical review. Frederiksen et al (2015) performed a meta-analysis on 39 studies and found significant effects of psychosocial interventions on ART clinical pregnancy and that reductions in anxiety were associated with improvement in pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hämmerli et al's (2009) meta-analysis found psychological interventions were effective at improving ART pregnancy rates but did not reduce depression or anxiety. Chow et al (2016) recently found evidence that psychosocial interventions improved psychological and pregnancy outcome in their critical review. Frederiksen et al (2015) performed a meta-analysis on 39 studies and found significant effects of psychosocial interventions on ART clinical pregnancy and that reductions in anxiety were associated with improvement in pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review focused on the identification of the human responses toward infertility and linked with the nursing diagnoses foci currently presented by NANDA‐I (Herdman & Kamitsuru, ). Previous literature reviews have endorsed the experience of infertility (Greil et al., ), the problems and needs of infertile patients (Hasanbeigi et al., ), and the psychosocial (Chow et al., ; Ying et al., ) and spiritual specificities of such phenomenon (Romeiro Caldeira, Brady, Timmins, et al.,2017; Roudsari, Allan, & Smith, ). This review is bringing an innovative approach based on nursing knowledge as represented in nursing standardized languages and classifications, such as NANDA‐I.…”
Section: Discussionmentioning
confidence: 99%
“…This multidimensional disturbance and the long-term effects patients endure seemed to legitimize a wide and integrated nursing patient-centered care capable of providing skillful support through all phases of the infertile experience (Ferland & Caron, 2013). This led to several developments of nurses and midwives intervention protocols (Barber, Egan, Ross, Evans, & Barlow, 1996), psychosocial approaches (Chow, Cheung, & Cheung, 2016), and the implementation of theoretical frameworks of practice such as Kolcaba's comfort (Schoener & Krysa, 1996) and Watson's human caring (Ozan & Okumuş, 2017). Yet, a proper nursing assessment and diagnosis responsible for setting the base for an effective sensitive and holistic care appears to be missing since little research on nursing diagnoses validation in infertile patients is available.…”
mentioning
confidence: 99%
“…According to reports by the World Health Organization in 2016, at least one of ten couples in developed countries cannot have children within five years of marriage, half of which are due to female infertility [1]. Oocyte activation inefficiency is a major problem causing female infertility [2].…”
Section: Introductionmentioning
confidence: 99%